Geotechnical aspects of underground construction in soft ground : Proceedings of the 7th International Symposium on Geotechnical Aspects fo Underground Construction in Soft Ground, Roma, Italy, 17-19 May, 2011 /: Proceedings of the 7th International Symposium on Geotechnical Aspects fo Underground Construction in Soft Ground, Roma, Italy, 17-19 May, 2011. (©2012) - Unknown
No abstract available